2020
DOI: 10.22454/fammed.2020.303653
|View full text |Cite
|
Sign up to set email alerts
|

Residency Scholarship Within Practice-based Research Networks

Abstract: Background and Objectives: Finding scholarship opportunities is a common struggle for family medicine residency programs, especially community-based programs. Participation in practice-based research networks (PBRNs) has been suggested as one option, but little is known about resident engagement in PBRNs. This study explores how PBRNs are currently involving family medicine residency programs and whether there are additional opportunities for engagement. Methods: We conducted a cross-sectional survey of 126 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Lack of time and knowledge emerged as the primary barriers, consistent with previous studies [ 17 , 18 ]. Competence was identified as a key motivational factor, aligning with the findings of previous studies [ 19 , 20 ]. Focused knowledge delivery through educational programs, guidebooks [ 21 ], and accessible online and offline formats within training hospitals is essential.…”
Section: Discussionsupporting
confidence: 84%
“…Lack of time and knowledge emerged as the primary barriers, consistent with previous studies [ 17 , 18 ]. Competence was identified as a key motivational factor, aligning with the findings of previous studies [ 19 , 20 ]. Focused knowledge delivery through educational programs, guidebooks [ 21 ], and accessible online and offline formats within training hospitals is essential.…”
Section: Discussionsupporting
confidence: 84%
“…National survey from 2011 looked at different factors [7]. Anecdotally, it is thought that residencies in a community hospital may have difficulty fulfilling these requirements as compared to tertiary care academic centers [5,8]. In community hospitals participation in practice based research network (PBRN) has been studied as one option by Weidner A et al for residents [8].…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotally, it is thought that residencies in a community hospital may have difficulty fulfilling these requirements as compared to tertiary care academic centers [5,8]. In community hospitals participation in practice based research network (PBRN) has been studied as one option by Weidner A et al for residents [8]. In places where residents were involved in research projects with PBRN, the residents generate research questions, study design, analyze data and help with manuscript writing, though the study found more residency faculty involvement than residents in PBRN and proposes it as an excellent opportunity for residents education and scholarly activity [8].…”
Section: Introductionmentioning
confidence: 99%
“…4 The article by Weidner et al in this issue of Family Medicine revisits this goal by focusing on the role that practice-based research networks (PBRNs) can play in building resident research, particularly in community-based programs. 5 Are PBRNs the answer to building resident research? They can provide opportunities for residents to participate in research.…”
mentioning
confidence: 99%
“…In fact, the study by Weidner about PBRNs wasn't really a PBRN study, but was actually a survey using the CERA infrastructure. 5 Including a resident in a project like this would be a great leveraging of infrastructure with an idea in a project that could be done in a matter of months.…”
mentioning
confidence: 99%